(untitled) (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2024)
In this study, active compound loaded stable nanoemulsion (surface charge -18 mV) was developed having small diameter (<100 nm) from the plant extract of raw Syzygium aromaticum, Ocimum tenuiflorum and rhizome of Zingiber officinale. The antimicrobial and antioxidant properties of formulated nanoemulsion were analyzed. The nanoemulsion showed good antimicrobial activity against various food poisoning organisms viz. bacteria (Staphylococcus aureus and Escherichia coli) and fungi (Candida albicans). For the antioxidant study, two different methods 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-Azino-bis(3-ethylbenzothiazoline-6-sulfonic 167 acid) diammonium salt (ABTS) were used, and a satisfactory result achieved (% inhibition for DPPH: 63.64±1.85 and ABTS: 48.36±1.12). The nanoemulsion in combination with a low dose of benzoic acid (200 ppm) is used as a preservative in formulated apple juice. The formulated juice quality was analyzed compared with standard fruit juice during a storage period of 30 days and quality of fruit juice remained good. This method thus allows reducing the use of synthetic preservatives with added benefit of natural beneficial compound in the formulated juice for human consumption.